Reading habits in the digital age: marketing strategies to promote reading among children and young adults - Dimitrova, Monika (2021)
Reading is a form of active learning, and cultivation of reading habits is vital for every child and young adult. However, according to the world’s most in-depth and trustworthy indicator of students’ abilities, PISA, reading skills among youngsters are barely improving. The project aims to deliver answers to the questions: what is the overall state of the reading habits of European children and young adults?; how is reading encouraged and promoted to children and young adults in the digital age?; what marketing and advertising strategies and initiatives are being introduced and practiced in Europe to encourage and promote reading among children and young adults?. To follow this aim we propose a survey overview on children’s and young adult’s reading habits and attitudes; bibliographical review of previous research on the topic of reading promotion, positive practices and marketing strategies; and a questionnaire survey, conducted among European organizations, involved in book and reading promotion. By observing the gathered data, we were able to conclude that reading habits and attitudes of children and young adults are predetermined at a very young age. The most important influencing factors that we examined were the active home literacy environment with access to books and literacy materials at an early age; the application of the reading aloud practice, starting at infancy; the kindergarten and school environment. What is more, we concluded that all adults, participating in children’s lives: parents; relatives; educators; librarians; social media influencers are role models with a strong influence on the shaping of the attitudes of youngsters towards reading.